Pengaruh Kualitas Corporate Governance terhadap Kinerja Perusahaan Publik (Studi Kasus Peringkat 10 Besar CGPI Tahun 2003, 2004, 2005) - Nur Sayidah (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2007)
The Purpose of this research is to examine the effect between corporate governance implementation quality and corporate performance. The samples of this re¬search is non banking companies which include the top ten of CGPI (Corporate Governance Perception Index) score in 2003, 2004 and 2005. The number of samples are 22 companies. A measure of corporate governance implementation quality is CGPI score by IICG (Indonesian Institute of Corporate Governance). A measure of corporate performance is profit margin (PM), ROA, ROE and ROI. The result of regression analysis shows significantly there are no effect between CGPI score and PM, ROA, ROE and ROI. It means that there are no effect between corporate gov¬ernance quality implementation and corporate performance. This result consistent with report of Hampel Committee (Short et.al, 1999) but controverse with findings of Klapper dan Love (2002) and Darmawati et. al (2005).Keywords: corporate governance, corporate performance, PM, ROA, ROE, ROI